Two-fold degeneracy of a class of rational Painlevé V solutions - Aratyn, H.; Gomes, J. F. [UNESP]; Lobo, G. V. [UNESP]; Zimerman, A. H. [UNESP] (My University, 2024)
We present a construction of a class of rational solutions of the Painlevé V Hamilton equations that exhibit a two-fold degeneracy, meaning that there exist two distinct solutions that share identical parameters. The fundamental object of our study is the orbit of translation operators of the A(1) 3 affine Weyl group acting on the underlying seed solution that only allows action of some symmetry operations. By linking points on this orbit to rational solutions, we establish conditions for such degeneracy to occur after involving in the construction additional Bäcklund transformations that are inexpressible as translation operators. This approach enables us to derive explicit expressions for these degenerate solutions. An advantage of this formalism is that it easily allows generalization to higher Painlevé systems associated with dressing chains of even period N > 4.
Keywords: Exactly Solvable and Integrable Systems; Nonlinear Sciences